BAI’ ‘ĪNAH DALAM KONSTRUKSI PEMIKIRAN SYĀFI’Ī - Agus Fakhrina (Jurnal Hukum Islam, 2015)
This study aims at analysing further and deeper on the concept of baiinah in Syafii thought construction. There were two research questions to be answered in this study: (1) whether or not Syafii allows the existence of hilah in trading; and (2) whether there are different concepts in which bai nah in hilah is allowed. To answer these questions, hermeneutikadilthey approach was employed in this research. Within this approach, the external and historical factors of a figure's historical life were taken into account. The result of the study indicated that there has been a misconception of how Syafii allowed baiinah. He actually allows the practice of qiyas and was against ulama who did not allow bai nah. The bai nah concept which was allowed by Syafii was not the trading in which contains dual trading intents; rather it was two trading which stand by themselves and did not relate with each other; thus avoiding misunderstanding within the trading process.